Mulheres transexuais e travestis negras: vulnerabilidade, preconceito e discriminação - Castro Siqueira, Gabriel (2021)
This article discusses experiences of prejudice and discrimination of black travestis and trans women and their coping strategies. This descriptive qualitative study examined the experiences of five participants in the age range of 25 to 47 years, living in Brazil. The findings suggest that black travestis and trans women experience high levels of vulnerability to violence due to perceived racial, sexual, and gender prejudice and discrimination. That often hinders their gender transition processes and disturbs their flourishing in their diversified identities. Religious belonging and participation in social movements are their main coping strategies to strengthen self-esteem, elaborate experiences of prejudice and discrimination, and explore their possibilities of womanhood or femininity. The creation or improvement of healthcare policies and practices designed with and for travestis and trans women is fundamental to their good living and to reduce their vulnerability to violence.